Ink-jet ink composition for textile printing

The inkjet ink composition, featuring self-dispersible carbon black and a specific water-dispersible urethane resin, addresses the challenges of viscosity stability and print quality in inkjet printing, achieving excellent concentration, fastness, and texture without pretreatment agents.

JP7662871B1Active Publication Date: 2025-04-15SAKATA INX
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024052017
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2025-04-15
Estimated Expiration
2044-03-27

AI Technical Summary

Technical Problem

Inkjet printing with pigment-containing inks faces challenges in achieving high concentration and viscosity stability of printed matter without using pretreatment agents, while maintaining fastness and texture.

Method used

The inkjet ink composition includes self-dispersible carbon black and a water-dispersible urethane resin with specific properties, such as elongation at break and tensile strength, along with resin-dispersed carbon black, to achieve balanced viscosity stability and print quality.

Benefits of technology

This composition results in excellent viscosity stability, concentration, fastness, and texture of printed matter, eliminating the need for pretreatment agents and enhancing overall printing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662871000001
    Figure 0007662871000001
  • Figure 0007662871000002
    Figure 0007662871000002
Patent Text Reader

Abstract

Provided is an ink-jet ink composition for textile printing, which has good viscosity stability and produces printed matter with excellent density, fastness and texture. [Solution] An inkjet ink composition for textile printing containing at least carbon black, a water-dispersible resin, and water, wherein the carbon black contains self-dispersible carbon black, the water-dispersible resin contains at least one water-dispersible urethane resin selected from the group consisting of polyether-based polyurethanes, polyester-based polyurethanes, and polycarbonate-based polyurethanes, the water-dispersible urethane resin has a breaking elongation of 700% or more and 1700% or less and a tensile strength of 30 MPa or less, and the content of the water-dispersible urethane resin is 100 parts by mass or more and 300 parts by mass or less in terms of solid content per 100 parts by mass of the carbon black.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ink-jet ink composition for textile printing. [Background technology]

[0002] 2. Description of the Related Art A method of printing a fabric by inkjet printing with an ink containing a pigment is known.

[0003] For example, Patent Document 1 discloses an inkjet ink for textile printing that contains a pigment, a water-dispersible resin, a crosslinking agent, and water, the water-dispersible resin having a breaking elongation of 1200-1800% and a tensile strength of 10-48 MPa is contained in an amount of 1.0-3.0 parts by mass per part by mass of the pigment, and the crosslinking agent is contained in an amount of 0.03-0.17 parts by mass per part by mass of the water-dispersible resin. It also shows that a printed matter (printed matter) printed with the inkjet ink for textile printing has excellent fastness and texture. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-031611 A Summary of the Invention [Problem to be solved by the invention]

[0005] Textile printing by inkjet printing using an ink composition containing a pigment tends to produce printed matter with a lower density than ink compositions containing a dye, but inks containing pigments have the advantage of being superior in fastness.

[0006] On the other hand, a technique of using a pretreatment agent to increase the concentration of an ink composition containing a pigment is known, but it is difficult to achieve a balance with fastness, which leads to increased costs and reduced productivity. Therefore, there has been a demand for an ink composition containing a pigment for ink-jet printing that can produce printed products with good concentration without using a pretreatment agent.

[0007] Furthermore, from the viewpoint of ejection properties by the inkjet method, ink compositions for textile printing are required to have a property of maintaining a constant viscosity (viscosity stability).

[0008] Therefore, an object of the present invention is to provide an inkjet ink composition for textile printing that is excellent in fastness and texture of the printed matter (textile print), as well as in density of the printed matter and viscosity stability of the ink composition. [Means for solving the problem]

[0009] The present invention is an inkjet ink composition for textile printing that contains at least carbon black, a water-dispersible resin, and water, wherein the carbon black contains self-dispersible carbon black, the water-dispersible resin contains at least one water-dispersible urethane resin selected from the group consisting of polyether-based polyurethanes, polyester-based polyurethanes, and polycarbonate-based polyurethanes, the water-dispersible urethane resin has a breaking elongation of 700% or more and 1700% or less and a tensile strength of 30 MPa or less, and the content of the water-dispersible urethane resin is 100 parts by mass or more and 300 parts by mass or less in terms of solid content per 100 parts by mass of the carbon black.

[0010] In the ink-jet printing ink composition of the present invention, it is preferable that the carbon black further contains resin-dispersed carbon black. The mass ratio of the self-dispersed carbon black to the resin-dispersed carbon black is preferably 1:5 to 5:1. Effect of the Invention

[0011] The present invention can provide an ink-jet ink composition for textile printing that has good viscosity stability and produces printed matter that is excellent in density, fastness, and texture. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The inkjet ink composition for textile printing of the present invention is an inkjet ink composition for textile printing that contains at least carbon black, a water-dispersible resin, and water, wherein the carbon black contains self-dispersible carbon black, the water-dispersible resin contains at least one water-dispersible urethane resin selected from the group consisting of polyether-based polyurethanes, polyester-based polyurethanes, and polycarbonate-based polyurethanes, and the water-dispersible urethane resin has a breaking elongation of 700% or more and 1700% or less and a tensile strength of 30 MPa or less, and contains 100 parts by mass or more and 300 parts by mass or less of the water-dispersible urethane resin in terms of solid content per 100 parts by mass of the carbon black.

[0013] The inkjet ink composition for textile printing of the present invention (hereinafter also referred to as the ink composition of the present invention) uses self-dispersing carbon black to obtain good density of printed matter, while optimizing the amount of water-dispersible resin having specific physical properties added makes it possible to achieve both fastness and texture of printed matter and storage stability of the ink composition. However, the present invention should not be construed as being limited to the above mechanism.

[0014] (Carbon Black) The ink composition of the present invention contains carbon black.

[0015] The carbon black contains self-dispersible carbon black. By containing the above-mentioned self-dispersible carbon black and the specific water-dispersible urethane resin, it is possible to obtain an ink composition that has good viscosity stability and produces printed matter with excellent density, fastness, and texture. The self-dispersing carbon black is carbon black that can be dispersed in water without using a pigment dispersant by chemically treating the surface of the carbon black to add hydrophilic functional groups such as carboxyl groups and phosphate groups.

[0016] Examples of the self-dispersing carbon black include carbon black having at least one hydrophilic group, such as a carbonyl group, a hydroxyl group, a carboxyl group, a sulfo group, or a phosphate group, or a salt thereof, introduced onto the surface of the carbon black by chemical bonding, either directly or via another group. Of these, carbon black having a carboxyl group or a phosphate group introduced on the surface is preferred, and from the viewpoint of providing suitable viscosity stability, carbon black having a carboxyl group introduced on the surface is more preferred.

[0017] The self-dispersing carbon black preferably has an average particle size of 300 nm or less, more preferably 200 nm or less, and even more preferably 150 nm or less. The "average particle size" is a volume-based average value in a particle size distribution measured by dynamic light scattering.

[0018] Examples of commercially available self-dispersible carbon black products include the CAB-O-JET series manufactured by Cabot Corporation, such as "CAB-O-JET200," "CAB-O-JET300," "CAB-O-JET400," "CAB-O-JET250C," "CAB-O-JET260M," "CAB-O-JET270," and "CAB-O-JET450C," and "BONJET BLACK CW-1," "BONJET BLACK CW-2," "BONJET BLACK CW-3," and "BONJET BLACK CW-4," manufactured by Orient Chemical Industries Co., Ltd.

[0019] The carbon black preferably further contains resin-dispersed carbon black. By including the resin-dispersed carbon black, it is possible to favorably impart fastness to printed matter. The resin-dispersed carbon black is carbon black to which dispersibility can be imparted by a pigment dispersant (resin).

[0020] Examples of carbon black that can be used for the resin-dispersed carbon black include furnace black, lamp black, acetylene black, and channel black.

[0021] As the pigment dispersant, it is preferable to use a polymer dispersant (resin dispersant). Examples of such pigment dispersants include acrylic acid-acrylonitrile copolymers, acrylic acid-acrylic acid alkyl ester copolymers, styrene-acrylic acid copolymers, styrene-methacrylic acid copolymers, styrene-acrylic acid-acrylic acid alkyl ester copolymers, styrene-methacrylic acid-acrylic acid alkyl ester copolymers, styrene-α-methylstyrene-acrylic acid copolymers, styrene-α-methylstyrene-acrylic acid copolymers-acrylic acid alkyl ester copolymers, styrene-maleic acid copolymers, and vinylnaphthalene-maleic acid copolymers, as well as inorganic salts or organic salts (neutralized products) of these. These pigment dispersants can be used alone or in combination of two or more. Among these, from the viewpoint of storage stability of the ink composition, a styrene-acrylic acid copolymer or a neutralized product thereof is preferred, and an acrylic acid / lauryl acrylate / styrene copolymer or a neutralized product thereof is more preferred.

[0022] From the viewpoint of storage stability of the ink composition, the pigment dispersant preferably has a weight average molecular weight of 15,000 or more and 50,000 or less, and more preferably 20,000 or more and 40,000 or less. In this specification, the "weight average molecular weight" is the weight average molecular weight measured by GPC (gel permeation chromatography) and converted into standard polystyrene.

[0023] From the viewpoint of storage stability of the ink composition, the pigment dispersant preferably has an acid value of 80 mgKOH / g or more and 180 mgKOH / g or less, and more preferably 100 mgKOH / g or more and 150 mgKOH / g or less. In this specification, the "acid value" refers to a theoretical acid value calculated arithmetically from the number of milligrams of potassium hydroxide theoretically required to neutralize 1 g of the unneutralized resin (pigment dispersant).

[0024] The pigment dispersant is preferably contained in an amount of 1 part by mass or more and 200 parts by mass or less relative to 100 parts by mass of the carbon black. The content of the pigment dispersant is more preferably 5 parts by mass or more, and even more preferably 60 parts by mass or less, relative to 100 parts by mass of the carbon black.

[0025] The method for preparing the dispersion of the resin-dispersed carbon black is not particularly limited. The dispersion may be prepared by adding carbon black to a varnish in which the pigment dispersant is dissolved, and using various dispersing machines, such as a ball mill, a bead mill, an attritor, a roll mill, a sand mill, or an agitator mill.

[0026] The mass ratio of the self-dispersed carbon black to the resin-dispersed carbon black is preferably 1:5 to 5:1. By setting the mass ratio of the self-dispersed carbon black to the resin-dispersed carbon black within the above range, it is possible to favorably impart fastness to printed matter. The mass ratio of the self-dispersed carbon black to the resin-dispersed carbon black is more preferably 1:4 to 1:1.

[0027] The carbon black may contain carbon black dispersed with a dispersant other than a surfactant or a resin dispersant, as long as the effects of the present invention are not adversely affected.

[0028] The content of the carbon black is, for example, preferably from 3% by mass to 20% by mass, and more preferably from 5% by mass to 15% by mass, relative to the total mass of the ink composition.

[0029] (Water dispersible resin) The ink composition of the present invention contains a water-dispersible resin.

[0030] The water-dispersible resin contains at least one water-dispersible urethane resin selected from the group consisting of polyether-based polyurethanes, polyester-based polyurethanes, and polycarbonate-based polyurethanes.

[0031] The water-dispersible urethane resin has a breaking elongation of 700% or more and 1700% or less. When the breaking elongation of the water-dispersible urethane resin is within the above range, the viscosity stability of the ink composition can be improved, and the texture of the printed matter can be imparted. The water-dispersible urethane resin preferably has a breaking elongation of 750% or more, more preferably 800% or more, and preferably has a breaking elongation of 1500% or less, more preferably 1200% or less.

[0032] The water-dispersible urethane resin has a tensile strength of 30 MPa or less. When the tensile strength of the water-dispersible urethane resin is within the above range, the viscosity stability of the ink composition can be improved, and the texture of the printed matter can be imparted. The tensile strength of the water-dispersible urethane resin is preferably 10 MPa or more, more preferably 15 MPa or more, and even more preferably 20 MPa or more.

[0033] In this specification, the "tensile strength" and "elongation at break" are determined by the following method. A water-dispersible urethane resin is applied onto a polytetrafluoroethylene sheet, dried at room temperature for 12 hours, and then dried at 60°C for a further 6 hours. The sheet is then peeled off to create a resin film made of the water-dispersible urethane resin with a thickness of 500 μm. Using a tensile tester [manufactured by Yasuda Seiki Seisakusho Co., Ltd.], the obtained resin film is pulled at a measurement temperature of 25° C. and a pulling speed of 200 mm / min, and the strength and elongation at the time of break are determined.

[0034] Examples of commercially available water-dispersible urethane resins include "IMPLANILE DLU" and "IMPLANILE DL1380" manufactured by Sumika Covestro Urethanes, "ADEKA BONTITOR HUX-282" manufactured by Adeka Corporation, "DAOTON TW6490" manufactured by Daicel Allnex Corporation, and "TAKELAC W-6061T" manufactured by Mitsui Chemicals, Inc.

[0035] The content of the water-dispersible urethane resin is 100 parts by mass or more and 300 parts by mass or less in terms of solid content relative to 100 parts by mass of the carbon black. By including the water-dispersible urethane resin in the above range, it is possible to impart fastness and texture to printed matter and viscosity stability to the ink composition. The water-dispersible urethane resin is preferably present in an amount of 125 parts by mass or more, and more preferably 150 parts by mass or more, in terms of solid content, per 100 parts by mass of the carbon black. The water-dispersible urethane resin is preferably present in an amount of 275 parts by mass or less, and more preferably 250 parts by mass or less, in terms of solid content, per 100 parts by mass of the carbon black.

[0036] (water) The ink composition of the present invention contains water.

[0037] The water content in the ink composition of the present invention is preferably, for example, from 30% by mass to 80% by mass.

[0038] (Organic solvent) The ink composition of the present invention may contain an organic solvent as necessary.

[0039] The organic solvent is preferably a water-soluble organic solvent. Examples of the water-soluble organic solvent include glycol ethers such as glycerin, dipropylene glycol dimethyl ether, and diethylene glycol ethyl methyl ether, glycol ether esters, alcohols, ketones, organic carbonates, and mixtures thereof.

[0040] The content of the organic solvent in the ink composition of the present invention is preferably, for example, from 15% by mass to 50% by mass.

[0041] (Surfactant) The ink composition of the present invention may contain a surfactant, if necessary.

[0042] The surfactant may be any of cationic, anionic, amphoteric and nonionic surfactants, which may be appropriately selected from known surfactants. Among these, nonionic surfactants are preferred from the viewpoint of storage stability of the ink composition.

[0043] The content of the surfactant in the ink composition of the present invention is preferably, for example, from 0.01% by mass to 1% by mass.

[0044] (others) Various additives may be added to the ink composition of the present invention as necessary. Specific examples of the additives include light stabilizers, surface treatment agents, antioxidants, antiaging agents, crosslinking accelerators, plasticizers, preservatives, pH adjusters, antifoaming agents, and moisturizing agents. These additives can be appropriately selected from known additives.

[0045] (Method of producing ink composition) The method for producing the ink composition of the present invention is not particularly limited, and the above materials may be mixed by stirring using a known method.

[0046] (Printed material) The substrate to be printed with the ink composition of the present invention may be any conventionally used fabric, and may be, for example, a fabric made of cotton, silk, linen, rayon, acetate, nylon or polyester fibers, or a blended fabric made of two or more of these fibers.

[0047] The method for printing the ink composition of the present invention is not particularly limited, and it is sufficient to print the ink composition on the above-mentioned substrate using a known inkjet printing device.

[0048] (Physical properties of ink composition) The ink composition of the present invention has good viscosity stability. In this specification, the viscosity stability is evaluated by the following method.

[0049] The ink composition is placed in a glass bottle, and the viscosity at 25° C. is measured using a viscometer (RE100L model manufactured by Toki Sangyo Co., Ltd.) After that, the bottle is sealed and stored at 60° C. for 4 weeks, and the viscosity (25° C.) after storage is measured using the same viscometer. The viscosity stability is evaluated based on the viscosity change rate [[(viscosity after 4 weeks at 60° C.−viscosity before storage) / (viscosity before storage)]×100]. If the rate of change in viscosity is 5% or less, the viscosity stability is evaluated as good, and if it is 3% or less, the viscosity stability is evaluated as extremely good.

[0050] The ink composition of the present invention has excellent density in printed matter. In this specification, the density of a printed matter is evaluated by the following method.

[0051] A solid image of the ink composition is printed on a 100% cotton white fabric using an evaluation printer equipped with a SPECTRA head, and then dried using a conveyor oven to prepare a print for evaluation. The image density (OD value) of the printed matter for evaluation is measured using a spectrophotometer (X-Rite eXact, manufactured by X-Rite Corporation). An OD value of 1.45 or greater is considered to be of excellent density, and an OD value of 1.5 or greater is considered to be of excellent density.

[0052] The ink composition of the present invention provides excellent fastness of printed matter. In this specification, the fastness of a printed matter is evaluated by preparing a printed matter for evaluation in the same manner as in the evaluation method for the density of the printed matter described above, and evaluating it through tests of fastness to washing, fastness to dry rubbing, and fastness to wet rubbing. If all tests pass or exceed the standard, the printed matter is deemed to have excellent fastness.

[0053] The washing fastness is evaluated by the following method. The above-mentioned evaluation prints are washed normally five times in a household washing machine (washing conditions: wash, spin, dry in normal mode), and the image density (OD value) of the prints before and after washing is measured using a spectrophotometer (X-Rite eXact, manufactured by X-Rite), and evaluated as the rate of change from the initial value (before washing). If the OD value after washing is 80% or more, it is rated as pass, and if it is 90% or more, it is rated as particularly excellent.

[0054] The dry rubbing fastness is evaluated by the following method. The printed surface of the evaluation print is rubbed 100 times with a bleached cloth under a load of 200 g using a Gakushin fastness tester (manufactured by Daiei Scientific Instruments Co., Ltd.) The degree of staining of the bleached cloth at that time is evaluated using the staining gray scale in accordance with JIS L 0805:2005. If the above evaluation is 3-4 grade or above, it is evaluated as passing, and if it is 4-5 grade or above, it is evaluated as particularly excellent.

[0055] The wet rubbing fastness is evaluated by the following method. The surface of the printed matter for evaluation is rubbed 100 times with a water-soaked bleached cloth under a load of 200 g using a Gakushin type fastness tester (manufactured by Daiei Scientific Instruments Co., Ltd.) The degree of staining of the bleached cloth at that time is evaluated according to JIS L 0805:2005 using the staining gray scale. If the above evaluation is 3-4 grade or above, it is evaluated as passing, and if it is 4-5 grade or above, it is evaluated as particularly excellent.

[0056] The ink composition of the present invention has excellent texture. In this specification, the texture is evaluated by preparing a print for evaluation in the same manner as in the evaluation method for the density of the print, and evaluating the texture by touch. A printed matter that bends easily but feels slightly stiffer than the fabric itself is rated as having an excellent texture, and a printed matter that bends easily and feels close to the softness of 100% cotton fabric itself is rated as having an especially excellent texture.

[0057] The present specification discloses the following:

[0058] The present disclosure (1) is an inkjet ink composition for textile printing that contains at least carbon black, a water-dispersible resin, and water, wherein the carbon black contains self-dispersible carbon black, the water-dispersible resin contains at least one water-dispersible urethane resin selected from the group consisting of polyether-based polyurethanes, polyester-based polyurethanes, and polycarbonate-based polyurethanes, the water-dispersible urethane resin has a breaking elongation of 700% or more and 1700% or less and a tensile strength of 30 MPa or less, and the content of the water-dispersible urethane resin is 100 parts by mass or more and 300 parts by mass or less in terms of solid content per 100 parts by mass of the carbon black. The present disclosure (2) relates to the inkjet ink composition for textile printing according to the present disclosure (1), in which the carbon black further contains resin-dispersed carbon black. The present disclosure (3) is the inkjet ink composition for textile printing according to the present disclosure (1) or (2), in which the mass ratio of the self-dispersed carbon black to the resin-dispersed carbon black is 1:5 to 5:1. EXAMPLES

[0059] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Unless otherwise specified, "%" means "% by mass" and "parts" means "parts by mass."

[0060] The materials used in the examples and comparative examples are as follows.

[0061] (Self-dispersing carbon black dispersion) Self-dispersing carbon black dispersion 1 (product name "CAB-O-JET300", manufactured by Cabot Corporation, pigment concentration 15% by mass, contains carboxyl groups) Self-dispersing carbon black dispersion 2 (product name "CAB-O-JET400", manufactured by Cabot Corporation, pigment concentration 15% by mass, contains phosphate groups)

[0062] (Resin-dispersed carbon black dispersion) 25 parts by mass of a pigment dispersant (acrylic acid / lauryl acrylate / styrene copolymer, weight average molecular weight 20,000, acid value 140 mgKOH / g) was dissolved in a mixed solution of 3.5 parts by mass of potassium hydroxide and 71.5 parts by mass of water to obtain an aqueous resin varnish containing the pigment dispersant with a solid content of 25% by mass. 73 parts by mass of water was added to 12 parts by mass of the above aqueous resin varnish and mixed, and 15 parts by mass of carbon black (product name "MA100", manufactured by Mitsubishi Chemical Corporation) was further added and mixed with stirring, and then milled in a wet circulation mill to prepare a resin-dispersed carbon black dispersion. The weight average molecular weight and acid value of the pigment dispersant were measured by the methods described herein.

[0063] (Water dispersible resin) Resin 1 (polycarbonate polyurethane, product name "Impranil DLU", manufactured by Sumika Covestro Urethane Co., Ltd., solid content 60% by mass, elongation at break 800%, tensile strength 30 MPa) Resin 2 (polyester polyurethane, product name "Impranil DL1380", manufactured by Sumika Covestro Urethane Co., Ltd., solid content 60% by mass, elongation at break 1200%, tensile strength 25 MPa) Resin 3 (polyether polyurethane, product name "ADEKA BONTITOR HUX-282", manufactured by ADEKA Corporation, solid content 55% by mass, elongation at break 1100%, tensile strength 25 MPa) Resin 4 (polyester polyurethane, product name "Impranil DLC-T", manufactured by Sumika Covestro Urethane Co., Ltd., solid content 35% by mass, elongation at break 500%, tensile strength 6 MPa) Resin 5 (polyester polyurethane, product name "ADEKA BONTITOR HUX-895", manufactured by ADEKA Corporation, solid content 48% by mass, elongation at break 900%, tensile strength 40 MPa) Resin 6 (polyether polyurethane, product name "NeoRez R-967", manufactured by Sumika Covestro Urethane Co., Ltd., solid content 40% by mass, elongation at break 600%, tensile strength 34.3 MPa) Resin 7 (polyester polyurethane, product name "Yodosol RA85", manufactured by Henkel Japan, solid content 40% by mass, elongation at break 400%, tensile strength 30 MPa) The breaking elongation and tensile strength of the water-dispersible resin were measured by the methods described in this specification.

[0064] (Surfactant) Surfactant 1 (product name "E1010", manufactured by Nissin Chemical Industry Co., Ltd.) Surfactant 2 (product name "Surfynol 440", manufactured by Nissin Chemical Industry Co., Ltd.)

[0065] (water) Water (purified water)

[0066] (Organic solvent) Glycerin

[0067] (Examples 1 to 8, Comparative Examples 1 to 7) <Preparation of Ink Composition> Each material was blended based on Tables 1 and 2, and stirred and mixed by a known method to prepare each ink composition. In addition, in Tables 1 and 2, "amount of resin relative to carbon black" means the content of water-dispersible urethane resin (parts by mass of solid content) relative to 100 parts by mass of carbon black.

[0068] <Viscosity stability> The prepared ink composition was placed in a glass bottle, and the viscosity at 25° C. was measured using a viscometer (RE100L manufactured by Toki Sangyo Co., Ltd.). Thereafter, the bottles were sealed and stored at 60° C. for 4 weeks, and the viscosity (25° C.) after storage was measured using the above viscometer. From the measured viscosities, the viscosity change rate [[(viscosity after 4 weeks at 60°C - viscosity before storage) / (viscosity before storage)] x 100] was calculated and evaluated according to the following criteria. The results are shown in Tables 1 and 2. (Evaluation Criteria) ⊚: Viscosity change rate was less than 3%. ◯: The viscosity change rate was 3% or more and less than 5%. ×: The viscosity change rate was 5% or more and less than 10%. XX: The viscosity change rate was 10% or more.

[0069] <Preparation of printed materials for evaluation> A solid image of the ink composition prepared was printed on a 100% cotton white fabric using an evaluation printer equipped with a SPECTRA head, and then dried using a conveyor oven to prepare a print for evaluation.

[0070] <Concentration> The image density (OD value) of the prints prepared for evaluation was measured using a spectrophotometer (X-Rite eXact, manufactured by X-Rite Corporation) and evaluated according to the following criteria. The results are shown in Tables 1 and 2. (Evaluation Criteria) ◎: OD value was 1.5 or more. ○: OD value was 1.45 or more and less than 1.5. ×: OD value was 1.4 or more and less than 1.45. ××: OD value was less than 1.4.

[0071] <Washing fastness> The evaluation prints were washed five times in a household washing machine (washing conditions: wash, spin-dry, and dry in normal mode), and the image density (OD value) of the prints before and after washing was measured using a spectrophotometer (X-Rite eXact, manufactured by X-Rite). The rate of change from the initial value (before washing) was used to evaluate the results according to the following criteria. The results are shown in Tables 1 and 2. (Evaluation Criteria) ⊚: OD value after washing was 90% or more of the initial value. ○: The OD value after washing was 80% or more and less than 90% of the initial value. ×: The OD value after washing was 70% or more and less than 80% of the initial value. XX: The OD value after washing was less than 70% of the initial value.

[0072] <Dry rubbing fastness> The printed surface of the evaluation print was rubbed 100 times with a bleached cloth under a load of 200 g using a Gakushin fastness tester (manufactured by Daiei Scientific Instruments Co., Ltd.). The degree of staining of the bleached cloth was evaluated using the staining gray scale according to JIS L 0805:2005 and the following criteria. The results are shown in Tables 1 and 2. (Evaluation Criteria) ◎: Grade 4-5 to 5. ○: Grade 3-4 to Grade 4. ×: Grade 2-3 to Grade 3. ××: Grade 2 or below.

[0073] <Wet rubbing fastness> The surface of the printed matter for evaluation was rubbed 100 times with a water-soaked bleached cloth under a load of 200 g using a Gakushin fastness tester (manufactured by Daiei Scientific Instruments Co., Ltd.). The degree of staining of the bleached cloth was evaluated using the staining gray scale according to JIS L 0805:2005 and the following criteria. The results are shown in Tables 1 and 2. (Evaluation Criteria) ◎: Grade 4-5 to 5. ○: Grade 3-4 to Grade 4. ×: Grade 2-3 to Grade 3. ××: Grade 2 or below.

[0074] <Texture> The prints prepared for evaluation were touched and evaluated according to the following criteria. The results are shown in Tables 1 and 2. (Evaluation Criteria) ◎: The print bends easily and is close to the softness of 100% cotton fabric. ○: The print is easily bent, but feels slightly stiffer than the fabric itself. ×: Printed matter feels stiff. ××: Printed material is too hard to bend freely

[0075] [Table 1]

[0076] [Table 2]

[0077] From Tables 1 and 2, it was confirmed that the ink compositions of the examples had good viscosity stability, and the density, fastness and texture of the printed matter were excellent. It was confirmed that. [Industrial Applicability]

[0078] It is possible to provide an inkjet ink composition for textile printing that has good viscosity stability and produces printed matter that is excellent in density, fastness, and texture.

Claims

1. An ink-jet ink composition for textile printing, comprising at least carbon black, a water-dispersible resin, and water, The carbon black contains self-dispersed carbon black and resin-dispersed carbon black, the water-dispersible resin contains at least one water-dispersible urethane resin selected from the group consisting of polyether-based polyurethanes, polyester-based polyurethanes, and polycarbonate-based polyurethanes; The water-dispersible urethane resin has a breaking elongation of 700% or more and 1700% or less and a tensile strength of 30 MPa or less, the content of the water-dispersible urethane resin is 100 parts by mass or more and 300 parts by mass or less in terms of solid content relative to 100 parts by mass of the carbon black, The mass ratio of the self-dispersed carbon black to the resin-dispersed carbon black is 1:4 to 1:

1. An ink-jet ink composition for textile printing.

Citation Information

Patent Citations

  • Ink for ink-jet printing

    JP2009030014A

  • Ink for textile printing inkjet

    JP2009215506A

  • Ink set for inkjet printing

    JP2010150453A

  • Ink set for inkjet printing

    JP2010150454A

  • Inkjet ink and printing method using the same

    JP2015183027A